1to10 – a Cost-effective Heat Supply Concept with Low Primary Energy Consumption for Multi-family Houses and Small Residential Areas. (June 2016) - Gohl, Natalie; Bauer, Dan; Drück, Harald
Abstract: This contribution introduces an innovative, sustainable heat supply concept. This concept, which is based on solar thermal and geothermal heat generation and advanced heat storage technologies, will be realized for the first time as a heat supply system for new apartment buildings. The key feature of the system is the fact, that on an annual basis only 1 kWh of electricity will be required to generate 10 kWh of heat. This contribution is focused on the presentation of the above described, newly developed system concept as well as first results of the design and simulation studies for a pilot heat supply system that is planned to be realized in a complex of three multi-family houses within a total living area of over 3 500 m 2 in the German city Crailsheim, which is located 80 km north-east of Stuttgart. The development of the concept is part of the research project '1to10 – Development, testing and demonstration of a sustainable, standardized solar-geothermal heat supply concept'. In the conceptual design phase of the project, theoretical work for the realization of such systems is performed.